Effect of Carboxymethylation on the Rheological Properties of Hyaluronan - Wendling, Rian J. (PLoS One, 2016)
Chemical modifications made to hyaluronan to enable covalent crosslinking to form a hydrogel or to attach other molecules may alter the physical properties as well, which have physiological importance. Here we created carboxymethyl hyaluronan (CMHA) with varied degree of modification and investigated the effect on the viscosity of CMHA solutions. Viscosity decreased initially as modification increased, with a minimum viscosity for about 30–40% modification. This was followed by an increase in viscosity around 45–50% modification. The pH of the solution had a variable effect on viscosity, depending on the degree of carboxymethyl modification and buffer. The presence of phosphates in the buffer led to decreased viscosity. We also compared large-scale production lots of CMHA to lab-scale and found that large-scale required extended reaction times to achieve the same degree of modification. Finally, thiolated CMHA was disulfide crosslinked to create hydrogels with increased viscosity and shear-thinning aspects compared to CMHA solutions.